(3EOGQI GdeMGaX GdGSJKeGQjI GdMOjKI (B/s - (3Gdehefj, ZGRj adGMs ((3YeGf(B: s (3OGQ GdefGgL(B, s, 2009)
(3ebOeI YGeI Yf GdeMGaX(B- (3GdfehPL GdYGdej dEOGQI GdeMGaX(B- (3GdYhGFO hGdeNGWQI(B- (3GdeMaXI GdESJKeGQjI hGdefaYI hefMfjGJ GdShGA(B- (3eNGWQ GdeMaXI hGdYhGed GdeDKQI YdjgG(B- (3caGAI GdShb(B- (3ENJjGQ GdeMaXI GdeKdi HhGSWI JMOjO GdNW GdaYGd HGdCQbGe(B- (3feGPL egeI ddeMGaXI GdESJKeGQjI(B- (3bjGS COGA GdeMGaXI GdESKeGQjI(B- (3GdeMGaX GdESJKeGQjI GdOhdjI(B- (3eDTQGJ GdShb hOhQgG aj EOGQI GdeMGaXs
(3GdeQGLY U(B.317s
Keywords: (3GdESJKeGQs; (3GdESJKeGQ GdeGdjs; (3GdChQGb GdeGdjIs